2014
DOI: 10.1016/j.cell.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Spliced X-Box Binding Protein 1 Couples the Unfolded Protein Response to Hexosamine Biosynthetic Pathway

Abstract: SUMMARY The hexosamine biosynthetic pathway (HBP) generates UDP-GlcNAc (uridine diphosphate N-acetylglucosamine) for glycan synthesis and O-linked GlcNAc (O-GlcNAc) protein modifications. Despite the established role of the HBP in metabolism and multiple diseases, regulation of the HBP remains largely undefined. Here, we show that spliced X-box binding protein 1 (Xbp1s), the most conserved signal transducer of the unfolded protein response (UPR), is a direct transcriptional activator of the HBP. We demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
407
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(429 citation statements)
references
References 52 publications
(80 reference statements)
20
407
0
2
Order By: Relevance
“…These findings suggest that aging is associated with a decline in the capacity of cells to activate these posttranslational modifications, particularly SUMOylation and O‐GlcNAcylation. Rapid activation of both modifications has been reported in various postischemic organs 6, 8, 27, 28, 29, 30. Notably, in the present study, these were the only posttranslational modifications that showed impaired activation in both brain and kidney of aged mice.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…These findings suggest that aging is associated with a decline in the capacity of cells to activate these posttranslational modifications, particularly SUMOylation and O‐GlcNAcylation. Rapid activation of both modifications has been reported in various postischemic organs 6, 8, 27, 28, 29, 30. Notably, in the present study, these were the only posttranslational modifications that showed impaired activation in both brain and kidney of aged mice.…”
Section: Discussionsupporting
confidence: 66%
“…Ischemia‐induced O‐GlcNAcylation, which was evident in all post‐CA/CPR organs that we studied herein, occurs downstream of the IRE1 UPR branch 8, 29. More important, this activation was severely impaired in both brain and kidney of aged mice.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…XBP1s is a direct transcriptional activator of the hexosamine biosynthetic (HBP) pathway, via Xbp1s-dependent transcription of genes coding for key, rate-limiting enzymes [157]. This UPR-HBP axis is triggered in a variety of stress conditions, including ischemia-reperfusion (I/R) injury, where acute stimulation of Xbp1s confers robust cardio-protection in part via induction of HBP.…”
Section: Pdmentioning
confidence: 99%